ARBITRASE DALAM SISTEM HUKUM DI INDONESIA (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
In Indonesia, according to the party dispute resolution process there are severalways that usually can be selected, such as: through litigation track procedure(court) or through non-line litigation (mediation, conciliation, negoisation,consulting, valuation experts, and arbitration). In connection with thearbitration or the arbitration institution, in fact it already exists and has beenpracticed for centuries. In this country, the arbitration also has been knownas one of  the alternative dispute resolution through non-litigation public.Arbitration clauses are created from those taken in the contract which theyhave agreed. Accordingly, the parties involved in the contract points can besolved by using the method of  dispute. Therefore, this article will discuss theappropriate choices regarding the settlement of  disputes through arbitrationin law / legal system in Indonesia.Di Indonesia menurut proses penyelesaian sengketa para pihak ada beberapacara yang biasanya bisa dipilih seperti: melalui prosedur jalur litigasi (pengadilan) atau melalui non-line litigasi (mediasi, konsiliasi, negoisation, konsultasi, valuasi ahli, dan arbitrase). Berkaitan dengan arbitrase atauarbitrase lembaga, sebenarnya itu sudah ada dan telah dipraktikkan selamaberabad-abad. Di negeri ini, arbitrase juga telah sudah dikenal sebagai salah satu alternatif  penyelesaian sengketa publik melalui non-litigasi. Arbitrasediciptakan dari klausul yang mereka diambil dalam kontrak yang merekasudah setuju. Dengan demikian, pihak-pihak yang terlibat dalam poinkontrak dapat diselesaikan dengan menggunakan metode sengketa. Olehkarena itu, artikel ini akan membahas sesuai pilihan mengenai penyelesaiansengketa melalui arbitrase dalam hukum/sistem hukum di Indonesia.